Respuesta :
Let x be the length of shortest leg of right triangle (in cm)
(x + 2) = length of longer leg
(x + 4) = length of hypotenuse Use c2 = a2 + b2 formula that links the 3 sides of the triangle.
Then:
(x + 4)2 = x^2 + (x + 2)2
(x^2 + 8x + 16) = x^2 + (x^2 + 4x + 4) - then combine terms on the right side
0 = x2 - 4x - 12 - factor it.
0 = (x - 6) ( x + 2)
Try (x + 2) = 0 which implies x = -2 cm, but you know the triangle side can't be negative, so remove this solution. Try this (x - 6) = 0 which implies x = 6 cm. So your right triangle has sides : 6 cm , 8 cm and 10 cm for the hypotenuse.
(x + 2) = length of longer leg
(x + 4) = length of hypotenuse Use c2 = a2 + b2 formula that links the 3 sides of the triangle.
Then:
(x + 4)2 = x^2 + (x + 2)2
(x^2 + 8x + 16) = x^2 + (x^2 + 4x + 4) - then combine terms on the right side
0 = x2 - 4x - 12 - factor it.
0 = (x - 6) ( x + 2)
Try (x + 2) = 0 which implies x = -2 cm, but you know the triangle side can't be negative, so remove this solution. Try this (x - 6) = 0 which implies x = 6 cm. So your right triangle has sides : 6 cm , 8 cm and 10 cm for the hypotenuse.
Let the length of the shorter leg of the triangle be x cm
So, the length of the longer leg is x+ 2 cm
the length of the hypotenuse = x+4 cm
Pythagorean theorem states that "The square of the hypotenuse is equal to the sum of squares of the other two sides."
Therefore,
(x+4)^2 = x^2 + (x+2)^2
x^2 + 8x + 16 = x^2 + x^2 +4x + 4
x^2 - 4x - 12=0
Let's factorize using splitting the middle term method,
x^2 - 6x + 2x - 12 =0
x(x-6) +2(x-6)=0
(x+2)(x-6)=0
x=-2 or x=6
As we have taken x as the length, it cannot be negative.
Therefore x= 6cm
Longer side = x+2 =6+2 = 8 cm
Hypotenuse = x + 4 = 6+4=10 cm
The sides are, 6cm, 8cm and 10 cm.